Working to Educate Global Citizens and Create Neighborly Communities Locally and Globally: Penn's Partnerships in West Philadelphia as a Democratic Experiment in Progress - Ira Harkavy; Matt Hartley; Joann Weeks; Rita Hodges (Laureate Education Inc, 2016)
In the rapidly accelerating global era in which we now live, human beings must solve a vast array of unprecedently complex problems. Perhaps the most complex and significant problems facing society today are persistent, widening, and increasingly destructive social, economic, and political inequality; globally destructive, man-made climate change; and increasingly frequent and savage terrorist acts.  Given their proclaimed dedication to critical intelligence, and their unique constellation of formidable resources to develop it, institutions of higher education, we submit, have a unique responsibility to help solve these problems-indeed all the problems intensified by globalization.